Analysis of Potential Development of Ornamental Koi Fish Business in Blitar City as a Form of Community Service - Nurida Finahari; Alfiana (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2020)
Blitar city has the potential of a superior product, which isnamely Koi fish farming. Koi fish are commodities have a potential market share with a relatively expensive sale value. This potential requires development and assistance activities because this business sector has its own problems. This article aims to analyze the potential development of the Koi ornamental fish business in Blitar district as a form of community service. The analysis was carried out with a literature-based review of research publications and community service. The results of the study were used as a reference for designing community service activities to develop the potential of Koi fish farming in the city of Blitar. The results of the analysis show that the results of research on hatchery and enlargement of Koi fish can be done by utilizing the surrounding natural resources. Community service activities are generally carried out for the technical aspects of cultivation, business management and marketing management. Development of Blitar Koi fish culture can be designed in the form of sustainable activities in accordance with the results of the analysis.